Understanding Vatavyadhi as a Sequelaeae of Metabolic Syndrome And Its Management - A Review - Aneesh, M S (International Research Journal of Ayurveda & Yoga, 2024)
The increasing occurrence of metabolic syndrome in children and teenagers is alarming due to the potential for significant long-term health issues. Recognizing and addressing this condition early are essential to avoid permanent harm. Traditional Ayurvedic perspectives offer valuable insights into this issue. Conditions such as Sthaulya (Obesity), Prameha (Diabetes), Shonita Dusti (Blood Impurity), and Dhamani Pratichaya (Vascular Diseases) share similarities with metabolic syndrome. These arise from excessive intake and accumulation (Santarpana nidana), leading to a build-up of Kapha (one of three senses of humor having unctuous property) and Medha (fat), eventually affecting other Doshas (humor) and multiple tissues. Ayurvedic treatments aim to manage these conditions, as they tend to be chronic and prone to complications, potentially progressing to Vatavyadhi (neurological disorders) over time. The interplay of kapha and medha in blocking channels (Margavarana) is a crucial consequence of these conditions, contributing to the development of vatavyadhi. This review article highlights the importance of early intervention and traditional Ayurvedic approaches in managing metabolic syndrome-like conditions in children and adolescents to prevent long-term complications.